Mama and Mommy and me in the middle - LaCour, Nina (Candlewick Press, 2022)
When her mother goes on a business trip, a little girl, who loves to sit between Mama and Mommy at the table, misses her a lot and feels empty until Mommy finally comes home, filling the void with love.